Savings, investment, and growth in Nepal: An empirical analysis - Aadersh Joshi; Sumit Pradhan; Jagadish Prasad Bist (Financial Innovation, 2019)
This study analyzes the relationship between savings, investment, and economic growth in Nepal over 1975-2016. The structural breaks in the variables have been accounted for using the (Zivot and Andrews's, J Bus Econ Stat 10: 251-270 1992) unit root test along with (Gregory and Hansen's, Oxf Bull Econ Stat 58: 555-560, 1996) cointegration approach. The ARDL approach to cointegration in the presence of structural breaks has also been utilized to analyze the long-and short-run dynamics of savings, investment, and growth in Nepal. The results show structural breaks in the real GDP per capita during 2001 when the Royal Massacre and a state of emergency have taken place in Nepal. After allowing for this structural break, evidence of a cointegration relationship amongst savings, investment, and economic growth was identified. The estimates of the ARDL approach suggest that investment has a significant and positive impact on economic growth. However, gross domestic savings have a negative impact on growth in the long run. These results clearly show weaknesses of the economy in mobilizing savings into productive sectors.
Keywords: 650; Savings; Investment; Economic Growth; Structural Break; ARDL Model